Adapting the eating disorder examination for use during pregnancy: Preliminary results from a community sample of women with overweight and obesity. Issue 5 (7th November 2016) - Emery, Rebecca L.; Grace, Jennifer L.; Kolko, Rachel P.; Levine, Michele D.
ABSTRACT: Objective: The Eating Disorder Examination (EDE) is a structured clinical interview that is widely used for assessing disordered eating. Although the EDE has been used in pregnant women, no standard pregnancy version has been developed. Accordingly, the present study aimed to document adaptations made to a pregnancy version of the EDE (EDE‐PV) and to describe the internal reliability of this adapted version. Method: Three major modifications were made in the development of the EDE‐PV. First, disordered eating was assessed during and prior to pregnancy to account for changes across the perinatal period. Second, items were adapted and rules governing ratings were altered to distinguish eating attitudes and behaviors that are considered normative during pregnancy from disordered eating. Third, several items were omitted. Results: The EDE‐PV was administered to 129 women with overweight and obesity who were between 12 and 20 weeks gestation. Women were 27.25 ( SD  = 5.48) years of age and 56% were African American. Women endorsed low levels of disordered eating on the EDE‐PV, and the internal reliability was similar to previous reports. Conclusion: These findings provide support for use of the EDE‐PV to assess disordered eating among pregnant women with overweight and obesity. © 2016 Wiley Periodicals, Inc.(Int J Eat Disord 2017; 50:597–601)